2019
DOI: 10.1093/annonc/mdz289
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer Index and prediction of benefit from extended endocrine therapy in breast cancer patients treated in the Adjuvant Tamoxifen—To Offer More? (aTTom) trial

Abstract: BackgroundExtending the duration of adjuvant endocrine therapy reduces the risk of recurrence in a subset of women with early-stage hormone receptor-positive (HR+) breast cancer. Validated predictive biomarkers of endocrine response could significantly improve patient selection for extended therapy. Breast cancer index (BCI) [HOXB13/IL17BR ratio (H/I)] was evaluated for its ability to predict benefit from extended endocrine therapy in patients previously randomized in the Adjuvant Tamoxifen—To Offer More? (aTT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
141
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(147 citation statements)
references
References 36 publications
4
141
0
2
Order By: Relevance
“…High vs Low likelihood of benefit from extended endocrine therapy that is reported separately from the prognostic results (19,21,22).…”
Section: Component Of Bci [Bci (H/i)] Is Based On the H/i Ratio And Pmentioning
confidence: 99%
See 2 more Smart Citations
“…High vs Low likelihood of benefit from extended endocrine therapy that is reported separately from the prognostic results (19,21,22).…”
Section: Component Of Bci [Bci (H/i)] Is Based On the H/i Ratio And Pmentioning
confidence: 99%
“…Author Manuscript Published OnlineFirst on October 27, 2020; DOI: 10.1158/1078-0432.CCR- Previous clinical validation studies for prediction of extended endocrine benefit and outcome have demonstrated significant interaction between BCI (H/I) and extended endocrine therapy with letrozole or tamoxifen following initial tamoxifen treatment (19,22). A key question regarding BCI clinical utility is the biomarker effect in postmenopausal patients treated with a contemporary standard of care that includes an AI component as part of primary adjuvant treatment.…”
Section: Component Of Bci [Bci (H/i)] Is Based On the H/i Ratio And Pmentioning
confidence: 99%
See 1 more Smart Citation
“…After demonstrating the effectiveness of an extended endocrine therapy [ 26 ], it became crucial to determine the risk factors for late recurrence in HR-positive breast cancer to guide individualized extended endocrine therapy. Although the optimal predictive factor to select patients who will benefit from extended endocrine therapy remains unclear, it is commonly suggested that the prognostic benefit of extended endocrine therapy can be maximized among patients with a high disease relapse risk [ 27 ]. Based on our results, patients with 25(OH)D deficiency after the 5-year adjuvant endocrine therapy may be considered appropriate candidates for extended endocrine therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Globally, a significant benefit from extended tamoxifen was demonstrated for patients that were classified as BCI (H/I)‐High (HR = 0.35; 95% CI 0.15‐0.86): The risk of recurrence was 27.0% and 37.2% for patients treated with 10‐ and 5‐year tamoxifen, respectively, demonstrating a significant absolute benefit of 10.2% for the reduction in the risk of recurrence. In contrast, there was no significant benefit from an additional 5 years of tamoxifen in patients that were classified as BCI (H/I)‐Low (HR = 1.07; 95% CI 0.69‐1.65) 7 . These results highlight the clinical validity of BCI for the prediction of endocrine response and its clinical utility in tailoring the prescription of extended endocrine therapy.…”
mentioning
confidence: 86%